Nursing guidelines for hospital highs in trauma ready service (Research, Society and Development, 2022)
The objective of the study was to identify the main guidelines for discharge by nursing in urgency and emergency trauma services. This is an integrative review carried out in the following databases: Virtual Health Library (VHL), American Medicine Library (PubMed), Scientific Electronic Library Online (SciELO), Scopus and Google Scholar, published from 2015 to 2020 From the results found, six categories of guidelines emerged: skin care; use of non-pharmacological measures for pain relief; guidelines focusing on comprehensiveness and multidisciplinarity of care; family and patient participation in the discharge process; post-discharge follow-up. Patients who attend urgent and emergency services, especially trauma, need a wide range of care and professionals to ensure their best recovery after discharge. The nurse, as part of the multidisciplinary team, is a protagonist in the planning and execution of discharge guidelines.